PEMBERDAYAAN SEKOLAH MELALUI KEGIATAN KKN PLP TEMATIK DI KOTA BONTANG: School Empowerment Through Thematic KKN PLP Activities in Bontang - Krisna Mastiadi; Muhammad Refi Zulkifli; Natasya Puteri Junaidi; Rahman Handriana; Reza Restu Priyai; Siti Aminah; Qonita Tamara Fadhilah Idrus; Sudarman (Wadah Inovasi Indonesia, 2022)
Making an impact on the community is one of the goals that must be achieved by universities. When Covid hit, thematic KKN activities were carried out online, the impact of which was much less pronounced than being done offline. The KKN conducted in Bontang City is focused on SMKN I Bontang. This activity lasted for almost 2 months and has successfully carried out various activities, including service activities in the curriculum, student affairs, entrepreneurship, Health unit and several competitions in order to welcome Indonesian Independence Day, as well as revitalizing the beauty of fishponds in the school environment. This activity is carried out by students and supervisors, both when planning programs, implementing various activities, and also evaluating activities. Everything went according to what had been planned.